Effects of（La,Sr） co-doping on electrical conduction and magnetic properties of BiFeO_3 nanoparticles - 刘莉 王守宇 殷子 刘卫芳 徐训岭 张闯 李秀 杨佳斌 (中国物理B：英文版, 2016)
Multiferroic material as a photovoltaic material has gained considerable attention in recent years.Nanoparticles（NPs）La_（0.1）Bi_（0.9-x）Sr_xFeO_y（LBSF,x = 0,0.2,0.4） with dopant Sr~（2＋）ions were synthesized by the sol–gel method.A systematic change in the crystal structure from rhombohedral to tetragonal upon increasing Sr doping was observed.There is an obvious change in the particle size from 180 nm to 50 nm with increasing Sr substitution into LBFO.It was found that Sr doping effectively narrows the band gap from～2.08 e V to～1.94 e V,while it leads to an apparent enhancement in the electrical conductivity of LBSF NPs,making a transition from insulator to semiconductor.This suggests an effective way to modulate the conductivity of BiFeO_（3-）based multiferroic materials with pure phase by co-doping with La and Sr at the A sites of BiFeO_3.